Seasonal trophic ecology of the dominant Antarctic coral Malacobelemnon daytoni (Octocorallia, Pennatulacea, Kophobelemnidae). (September 2017) - Servetto, N.; Rossi, S.; Fuentes, V.; Alurralde, G.; Lagger, C.; Sahade, R.
Abstract: Antarctic ecosystems present highly marked seasonal patterns in energy input, which in turn determines the biology and ecology of marine invertebrate species. This relationship is stronger at lower levels of the food web, while upper levels may be less dependent on primary production pulses. The pennatulid Malacobelemnon daytoni, is one of the most abundant species in Potter Cove, Antarctica. In order to assess its trophic ecology and energetic strategies, its biochemical (carbohydrates, proteins and lipids), Fatty Acid (FA) and Stable Isotope (SI) (δ 15 N and δ 13 C) compositions were studied over a year-round period. The FA and SI profiles suggest an omnivorous diet and opportunistic feeding strategy for the species. These results, together with biochemical analysis (higher lipid and carbohydrate concentration observed in July and October 2009), support the hypothesis that resuspension events may be an important source of energy, reducing the seasonality of food depletion periods in winter. The evidence presented here gives us a better insight into the success that this species has in Potter Cove and under the current environmental changes experienced by the Antarctic Peninsula. Highlights: Malacobelemnon daytoni has a wide variety of food sources indicating an omnivorous diet and opportunistic feeding strategy. Resuspension events could be an important source of energy, reducing the seasonality of food depletion periods in winter. The feeding strategy observed give us a better insight of the ecological success that this specie has in Potter Cove.